ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KESADARAN K3 KARYAWAN PADA INSTALASI ARCHITECTURAL FURNITURE DI PT CANDI GUNA MANDIRI - Ananda Aulia, Lily; Zetli, Sri (Computer Science and Industrial Engineering, 2025)
Occupational Safety and Health (OSH) is a crucial aspect in ensuring the well-being of workers and supporting productivity and the continuity of work processes. However, at PT Candi Guna Mandiri, particularly within the Architectural Furniture installation division, there are still indications of low employee awareness regarding OSH practices, which may increase the risk of workplace accidents. This study aims to analyze the factors influencing employee awareness of OSH, including knowledge, attitude, training, managerial supervision, age, and work experience. The research uses a quantitative approach with a descriptive-analytic design and total sampling involving 79 respondents. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was conducted using the Spearman correlation test. The results showed that among the six independent variables examined, only two had a statistically significant relationship with OSH awareness: training (r = 0.279; r = 0.013) and managerial supervision (r = 0.410; r = 0.000). Other variables - knowledge, attitude, age, and work experience - did not show a significant correlation. It can be concluded that OSH awareness among employees is more influenced by institutional approaches, such as effective training and consistent supervision. Therefore, the company is advised to strengthen its training and supervision systems to foster a work culture that is more aware of occupational safety and health.